2020
DOI: 10.1111/nyas.14370
|View full text |Cite
|
Sign up to set email alerts
|

Exploring food security and nutrition among young women in the formally regulated garment sector of Myanmar

Abstract: Malnutrition can adversely influence women's overall health and development and that of their children. In the Yangon region of Myanmar, young women aged 15-19 years can be excessively thin, overweight, or anemic. A significant proportion of these young women working within the formal sector are employed in the garment industry. This study used a mixed-method approach to generate robust evidence on food security and nutrition in young female garment workers. The research revealed that women have poor quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Those who start working early after high school may have more disposable income—although their decision to start working may relate to their lower economic class; alternately, they may have less time for preparing meals. A study in Myanmar found that a key risk factor for not meeting the minimum dietary diversity among young women was employment 10 . In addition, the diet of factory workers who spend a large part of their time in the workplace and eat at least one of their daily meals there may be influenced by workplace environment and policy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Those who start working early after high school may have more disposable income—although their decision to start working may relate to their lower economic class; alternately, they may have less time for preparing meals. A study in Myanmar found that a key risk factor for not meeting the minimum dietary diversity among young women was employment 10 . In addition, the diet of factory workers who spend a large part of their time in the workplace and eat at least one of their daily meals there may be influenced by workplace environment and policy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Formal policies and regulations that promote nutrition in the workplace and that are sensitive to gender norms can help improve the situation (7,11,14,28). Keen attention should be paid to the vulnerabilities women face and the gender norms that constrain men's and women's roles in a healthy workplace and home.…”
Section: Discussionmentioning
confidence: 99%
“…At the most proximate, biological level, the type and amount of work undertaken by an individual will determine energy requirements, and women and men have different nutritional needs at different stages of the lifecycle (14). Working women do not necessarily need fewer calories than men, as they may work longer hours and have caretaking and household responsibilities in addition to their paid work, women of childbearing age are more vulnerable to anaemia and osteoporosis than men, and pregnant and lactating women require extra calories and folic acid for optimal physical and congenital development of their babies (5).…”
Section: Gendered Norms and Practicesmentioning
confidence: 99%
See 2 more Smart Citations